Enhancing Farmer Capacity Through Socialization and Training on Biosaka Elicitor Production in Telaga Biru District, Gorontalo Regency - Merita Ayu Indrianti; Moh Muchlis Djibran; Yusriyah Atikah Gobel; Aditya Djaini (Pascasarjana Universitas Mataram, 2025)
This community service activity aims to improve the capacity of farmers through socialization and training in the production of Biosaka elicitors in Telaga Biru District, Gorontalo Regency. Biosaka is a natural elicitor produced by the manual crushing of healthy plants in pure water, not fertilizers, hormones, or enzymes, thereby triggering the plant's natural defense response and holistically improving soil health. The activity was carried out on April 26, 2024, at the local Agricultural Extension Center (BPP), involving a group of farmers selected based on their high dependence on synthetic chemical inputs. The methodology of the activity combined interactive lectures, reflective discussions, and hands-on training guided by agricultural extension workers. The results showed that all participants were able to correctly understand the concept of Biosaka and successfully produced the elicitor independently with consistent quality—characterized by visual features (no sedimentation, no foaming, thick and shiny appearance) and an increase in the average Total Dissolved Solids (TDS) value of 250–350 ppm. Beyond the technical aspects, this activity built collective awareness of the importance of reducing dependence on chemical fertilizers and transitioning to sustainable agricultural practices based on local resources. By actively involving farmers and supported by local agricultural extension workers, this activity became the first step towards realizing more independent, environmentally friendly, and equitable agriculture in Telaga Biru District.